UPAYA PENINGKATAN KEMAMPUAN MENGGUNAKAN HURUF KAPITAL DALAM MENULIS TEKS BERITA DENGAN METODE INQUIRY - Gunarsa, I Kadek (Universitas Wijaya Kusuma Surabaya, 2020)
This study aims to describe efforts to increase the ability to use capital letters. The method used is descriptive qualitative in the form of classroom action research. The ability of students to use capital letters in writing news texts after applying the inquiry method has always increased. In cycle I the average score of students was 64.64, with details of 1 student getting a score of 88.8 which is included in the very good category, 9 students got a score of 77.7 which is included in the good category, 15 students got a score of 66.6 including in the sufficient category and 9 students scored below 66.6. In the second cycle the students' average score increased to 77.70, with details of 9 students getting a score of 88.8 which was included in the very good category, 16 students got a score of 77.7 which was in the good category, and 9 students got a score of 66, 6 is in the enough category